Pattern of mother–child feeding interactions in preterm and term dyads at 18 and 24 months - Salvatori, Paola; Andrei, Federica; Neri, Erica; Chirico, Ilaria; Trombini, Elena (Frontiers in Psychology, 2015)
Literature on mother-child feeding interactions during the transition to self-feeding in preterm populations is lacking, particularly through observational methods. The present research study aims to look at the longitudinal patterns of mother- toddler feeding interactions, comparing preterm and full term dyads. To this end, a multi-method approach was used to collect data from 27 preterm and 20 full-term toddlers and their mothers. For each dyad, mother-child interactions were observed during the snack time at 18 and 24 months of age and then assessed through the Italian version of the Feeding Scale. Higher scores on the scale indicate a less healthy pattern of interaction. Additionally, at both points in time, mothers completed the BDI-II questionnaire as a screen for maternal depression and the child’s developmental stage was assessed using the Griffiths Scales. A series of repeated measures ANOVAs were run to detect differences in feeding interactions between the two groups at the time of assessment. Our results show that preterm dyads report overall higher levels of maternal negative affection, interactional conflicts and less dyadic reciprocity during the meal compared to full-term dyads. Additionally, longitudinal data show that dyadic conflict decreases in both groups, whereas the child’s food refusal behaviors increase in the preterm group from 18 to 24 months. No differences were reported for both the BDI-II and the child’s development for the two groups. The results reveal that regardless of maternal depression and the child’s developmental stage, the two groups show different trajectories in the pattern of feeding interactions during the transition to self –feeding, at 18 and 24 months, with overall less positive interactions in preterm mother-child dyads.